The Herschel-SPIRE instrument and its in-flight performance* - Griffin, M. J.; Abergel, A.; Abreu, A.; Ade, P. A. R.; André, P.; Augueres, J.-L.; Babbedge, T.; Bae, Y.; Baillie, T.; Baluteau, J.-P.; Barlow, M. J.; Bendo, G.; et al. (Astronomy & Astrophysics, 2010)
n/a